1995
DOI: 10.1073/pnas.92.8.3254
|View full text |Cite
|
Sign up to set email alerts
|

Two routes of chlorophyllide synthesis that are differentially regulated by light in barley (Hordeum vulgare L.).

Abstract: NADPH-protochlorophyllide oxidoreductase (POR; EC 1.6.99.1) catalyzes the only known light-dependent step in chlorophyll synthesis of higher plants, the reduction of protochlorophyllide (Pchlide) to chlorophyllide. In barley, two distinct immunoreactive POR proteins were identified. In contrast to the light-sensitive POR enzyme studied thus far (POR-A), levels of the second POR protein remained constant in seedlings during the transition from dark growth to the light and in green plants. The existence of a sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
202
1
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 197 publications
(211 citation statements)
references
References 30 publications
7
202
1
1
Order By: Relevance
“…However, our recent results obtained for PORA of barley (Reinbothe et al, 1995 a, b and unpublished results) demonstrate that protein translocation can also be a specific regulatory step during lightinduced chloroplast development.…”
Section: Morphological Cellular and Molecular Events During The Ligmentioning
confidence: 99%
See 4 more Smart Citations
“…However, our recent results obtained for PORA of barley (Reinbothe et al, 1995 a, b and unpublished results) demonstrate that protein translocation can also be a specific regulatory step during lightinduced chloroplast development.…”
Section: Morphological Cellular and Molecular Events During The Ligmentioning
confidence: 99%
“…PORA is virtually absent both from rapidly greening and fully light-adapted plants, in which continuous photoreduction of Pchlide to Chlide must occur to sustain chlorophyll synthesis. However, recent results have solved this apparent paradox, as they have shown that there is a second Pchlide-reducing enzyme, termed PORB, which is constitutively expressed in etiolated, illuminated, and fully green barley plants (Holtorf et al, 1995).…”
Section: Morphological Cellular and Molecular Events During The Ligmentioning
confidence: 99%
See 3 more Smart Citations